Huawei’s Internationalization Process And Its Competitive Position In Foreign Markets: The Demand For Mobile Devices In The Modern Era - Dhay Al Shami; Cristian Camilo Marin Giraldo; Haneen Saleh Almekhlef; Asbaa Abdullah Aldabbous (AIBPM Publisher, 2019)
This paper is aimed at making a brief analysis to the internationalization process that Huawei has undertaken making a PEST analysis on the general framework on which the company is operating. From this analysis this team concluded that there is a moderate-risk level political and economical environment for the company arising from diplomatic tensions between the United States and China and the recent tarde war. During the analysis, we also drew the conclusion that the R&D centers of Huawei around the world and the demand for mobile devices are crucial for its economic performance. We were also able to establish the characteristics of the demand for mobile devices today from which our proposal to the company arises. According to the research we did, the demand for mobile devices is going to be strengthened by new users in younger ages and the replacement of the old devices that have fulfilled their product lifecycle. Therefore, our idea is to tackle this segment of the demand designing products or services for younger users taking advantage of the capabilities of the company in R&D. In Chapter 4 we analyzed the risks of getting this new product to the American market. The main risk which arises from the political difficulties of China and the US is the imposition of tariffs for the mobile devices coming from China. In that chapter we propose diffe The risks of trying to get this new product to the American market are described. We also offer three different alternatives to sort out the increase in tariffs. The most suitable option for Huawei is to diversify its production to Peru. This country has an FTA with the US which means that tariffs can be avoided, it is strong in mining which means that the raw material are available there and the labor force price is still competitive.